2022
DOI: 10.1101/2022.02.02.22270312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell genomics improves the discovery of risk variants and genes of Atrial Fibrillation

Abstract: Genome-wide association studies (GWAS) have linked hundreds of loci to cardiac diseases. However, in most loci the causal variants and their target genes remain unknown. We developed a combined experimental and analytical approach that integrates single cell epigenomics with GWAS to prioritize risk variants and genes. We profiled accessible chromatin in single cells obtained from human hearts and leveraged the data to study genetics of Atrial Fibrillation (AF), the most common cardiac arrhythmia. Enrichment an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…Multiple single-cell sequencing studies have reinforced the central role of atrial cardiomyocytes in atrial fibrillation biology [30,31]. A subset of atrial fibrillation risk variants has also been mapped to genes expressed in fibroblasts and immune cells [30], consistent with emerging hypotheses that both cardiac fibrosis and immune dysregulation can contribute to atrial fibrillation risk. In a single-cell sequencing study of patient-derived cardiac biopsies, the serine-threonine protein kinase PLK2 in cardiac fibroblasts was linked to atrial fibrillation through mechanisms related to increased inflammation and fibrosis [32 && ].…”
Section: Advances In Translational Researchmentioning
confidence: 63%
See 1 more Smart Citation
“…Multiple single-cell sequencing studies have reinforced the central role of atrial cardiomyocytes in atrial fibrillation biology [30,31]. A subset of atrial fibrillation risk variants has also been mapped to genes expressed in fibroblasts and immune cells [30], consistent with emerging hypotheses that both cardiac fibrosis and immune dysregulation can contribute to atrial fibrillation risk. In a single-cell sequencing study of patient-derived cardiac biopsies, the serine-threonine protein kinase PLK2 in cardiac fibroblasts was linked to atrial fibrillation through mechanisms related to increased inflammation and fibrosis [32 && ].…”
Section: Advances In Translational Researchmentioning
confidence: 63%
“…By simultaneously quantifying gene expression and chromatin accessibility at the single-cell level, atrial fibrillation risk loci can be linked to the individual cell types which are most affected by variants in these regions. Multiple single-cell sequencing studies have reinforced the central role of atrial cardiomyocytes in atrial fibrillation biology [30,31]. A subset of atrial fibrillation risk variants has also been mapped to genes expressed in fibroblasts and immune cells [30], consistent with emerging hypotheses that both cardiac fibrosis and immune dysregulation can contribute to atrial fibrillation risk.…”
Section: Advances In Translational Researchmentioning
confidence: 63%
“…We briefly discuss potential directions for future work. First, recent studies have shown that incorporating functional annotation in the prior distribution can improve the fine-mapping precision 33,79,104 . SuShiE currently employs a uniform distribution for prior causal probability.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, coupled with GWAS, single-cell genomics enabled prioritization of risk variants and genes in single cells obtained from human hearts and identified putative causal variants at 122 atrial fibrillation-associated loci. 21 These studies illustrate a general framework for integration of single-cell epigenomics with GWAS to reveal the relative contributions of distinct cell types to diseases and identify genes likely to be associated with complex traits.…”
Section: Bulk and Single-cell Omics Approachesmentioning
confidence: 99%